METHODOLOGY OF INCREASING STUDENTS' INTEREST IN THE SCIENCE OF PHYSICS BY SOLVING OLYMPIC PROBLEMS IN SPECIALIZED SCHOOLS - Shermurod Shamsiddinugli Isroilov (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the features of Olympiad problems in physics in specialized schools, necessary for preparing students of specialized schools for the Olympiad, analyzes knowledge of mathematics and provides examples of methods for solving several Olympiad problems.